2020
DOI: 10.4103/atm.atm_286_20
|View full text |Cite
|
Sign up to set email alerts
|

Anti-interleukin-6 monoclonal antibody for cytokine storm in COVID-19

Abstract: Novel coronavirus disease 2019 (COVID-19) is known to cause severe pneumonia and acute respiratory distress syndrome which may lead to death. Several treatments have been tested in the race to find a treatment regimen for this deadly viral infection. Tocilizumab, a recombinant humanized anti-interleukin-6 receptor monoclonal antibody, has been used and found to be beneficial in patients with COVID-19 and in cytokine storm. We present the case of a young, otherwise healthy male, presenting with COVID-19 and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Capoferri et al found in their studies that of the inflammatory markers, interleukin‐6 had the strongest correlation with relative bradycardia and other arrhythmias 7 . Interleukin‐6 is a significant inflammatory marker associated with the cytokine storm seen in COVID‐19 infection and has been reported to have direct impact on the sinoatrial node causing increased vagal tone and minimized heart rate variability ultimately leading to relative bradycardia 27‐29 . In addition to these hypotheses, as the disease course worsens arrhythmias are likely worsened by the hypoxia and multiorgan failure, resulting in electrolyte derangements and buildup of toxic metabolites 5,10 …”
Section: Mechanism Of Cardiac Involvementmentioning
confidence: 99%
“…Capoferri et al found in their studies that of the inflammatory markers, interleukin‐6 had the strongest correlation with relative bradycardia and other arrhythmias 7 . Interleukin‐6 is a significant inflammatory marker associated with the cytokine storm seen in COVID‐19 infection and has been reported to have direct impact on the sinoatrial node causing increased vagal tone and minimized heart rate variability ultimately leading to relative bradycardia 27‐29 . In addition to these hypotheses, as the disease course worsens arrhythmias are likely worsened by the hypoxia and multiorgan failure, resulting in electrolyte derangements and buildup of toxic metabolites 5,10 …”
Section: Mechanism Of Cardiac Involvementmentioning
confidence: 99%
“…Similarly to anakinra and corticosteroids, TCZ has been employed as supportive therapy in COVID-19 to manage symptoms of hyper-inflammation and other immune responses. Several published case series and reports observed remarkable clinical responses following the use of TCZ in COVID-19 patients, including the clinical resolution of septic shock, reduction in the markers of inflammation, enhanced negative conversion, and reduced need for invasive mechanical ventilation [128][129][130][131][132][133][134][135][136][137][138][139].…”
Section: Tocilizumabmentioning
confidence: 99%
“…Patient experienced remarkable recovery and was discharged to home 5 days after TCZ use. [133] TCZ; case series 5 critically ill COVID-19 patients whose illness was refractory to standardized treatment.…”
Section: Drug and Study Type Description Findings Referencesmentioning
confidence: 99%
“…Coronavirus 2019 (COVID-19) became a public health international emergency in December 2019 leading to hundreds of thousands of deaths to date [ 1 , 2 ]. COVID-19, caused by an enveloped RNA virus, is known to cause severe pneumonia with complications that lead to acute respiratory distress syndrome (ARDS), cytokine storm, and disseminated intravascular coagulation (DIC) [ 1 , 3 - 5 ]. Several cases have reported spontaneous pneumomediastinum and pneumothorax secondary to COVID-19; however, the underlying pathophysiology remains to be understood and pneumopericardium still remains uncommon [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%